(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Thermally modification processes change mechanical properties of wood. These changes depend on the temperature treatment. In this article are reported mechanical properties changes in spruce, beech and poplar wood, modified in temperature 200 °C sunflower oil. It is determined: density, bending strength, compressive strength on fiber direction, sharing strength on fiber direction, splitting strength on received wood according to BDS 16987:89. About comparison are studied mechanical properties of untreated samples. It is proven that the modified wood in sunflower oil has lower density and lower bending strength in parallel comparing with untreated wood.